2008
DOI: 10.1021/om800300k
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Trifluoromethylation Reactions at Nickel: A Structural and Reactivity Study

Abstract: A variety of nickel(aryl)(CF 3 ) complexes supported by a chelating bisphosphine were successfully prepared in order to investigate the possibility of reductive elimination of Ar-CF 3 . The first structural comparison of a Ni-CF 3 complex with a Ni-CH 3 complex is also presented. All of the new nickel(aryl)(CF 3 ) complexes were thermally stable and did not produce Ar-CF 3 under thermal conditions. Additives had very little effect on the reductive eliminations, although water was found to afford product in 22%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 41 publications
6
76
0
Order By: Relevance
“…Since [Ni(tpy)Br2] is reduced at the lowest potential (−1.30 V), compared with the other metal complexes studied in this work (e.g., (−1.12 V for [Ni(bpy)Br2]), the yields of the cross-coupling product with [Ni(tpy)Br2] participation are relatively higher (up to 73%) [72]. [95,96]. Instead, the Ni(II) σ-complexes 29 transmetalate copper halide species to yield [Cu(II)(L)(R F )(aryl)] 32.…”
Section: Aromatic Perfluoroalkylation Using Ni-tpy Under Electrocatalmentioning
confidence: 75%
“…Since [Ni(tpy)Br2] is reduced at the lowest potential (−1.30 V), compared with the other metal complexes studied in this work (e.g., (−1.12 V for [Ni(bpy)Br2]), the yields of the cross-coupling product with [Ni(tpy)Br2] participation are relatively higher (up to 73%) [72]. [95,96]. Instead, the Ni(II) σ-complexes 29 transmetalate copper halide species to yield [Cu(II)(L)(R F )(aryl)] 32.…”
Section: Aromatic Perfluoroalkylation Using Ni-tpy Under Electrocatalmentioning
confidence: 75%
“…We used the cis complexes as a starting point, as studies suggested these to be the predominant species in solution. [5,7,8] We applied a QM/QM' computational approach [11] with the layer partitioning A or B, or full geometry optimizations of the complexes. Figure 1 illustrates the…”
Section: Resultsmentioning
confidence: 99%
“…[6] Similarly, Ni II complexes also gave only poor conversions to ArCF 3 when 1,2-bis(diisopropylphosphino)ethane (DIPPE) bidentate ligands were employed. [8] Reductive eliminations from similar complexes bearing a CH 3 group instead of CF 3 , in contrast, are facile. [7,9] We applied computational studies [10] to explore the origins of these observations, particularly to understand the remarkable effect of Xantphos in the reductive elimination of [Pd…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic trifluoromethylation of non-activated organic halides represents a long-standing goal in organometallic chemistry [1][2][3][4][5][6][7][8][9][10]. The ability to introduce a trifluoromethyl group into a molecule of interest at a late stage of a synthesis using mild conditions alleviates the need to carry the fluorine functional group through potentially incompatible synthetic procedures, thereby eliminating potential side-reactions and raising overall yields.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the intense commercial and scientific interest in trifluoromethylation reactions, several key studies have highlighted some of the problematic steps of catalysis [1][2][3][4]17]. Perhaps most well-documented is the difficulty in reductive elimination of Ar-CF 3 from low valent Group 10 metal centers, which poses a serious challenge to the development of new catalysts for the trifluoromethylation of aryl bromides and chlorides [1,4,17].…”
Section: Introductionmentioning
confidence: 99%